Manajemen Layanan Khusus Dalam Lembaga Pendidikan - Nadilla Aleyda Maqhfira Agustin; Ainun Wafiq; Nur Ratih (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Education serves as a cornerstone for developing high-quality human resources, with educational management being the key to its success. Educational management encompasses planning, organizing, implementing, and evaluating to achieve goals aligned with students' needs, supporting efficient and effective learning processes. Special services, such as counseling, libraries, laboratories, extracurricular activities, school health services, cafeterias, cooperatives, transportation, dormitories, acceleration programs, and inclusive education, are designed to accommodate the diverse needs of students, including those with special needs. This study employs a descriptive qualitative approach through a literature review. Data were collected from various relevant journals, articles, and books, analyzed using content analysis. The findings indicate that managing special services requires stakeholder collaboration, systematic planning, and curriculum harmonization to realize fair and high-quality inclusive education, optimally supporting students' potential, talents, and interests. Special education service management, as part of school-based management, is designed to provide optimal services to students through various offerings, ensuring educational goals are achieved.